Guaranteed hierarchical reinforcement learning - Ang, Riley Xile (Nanyang Technological University, 2024)
Reinforcement learning (RL) is a sub-field of machine learning that aims to train an agent in an interactive environment to sequentially make choices via a process of trial-and-error, to maximize a total reward over time.